Strategi Komunikasi Humas dalam Meningkatkan Citra Positif Pemerintahan Desa Bagorejo Kecamatan Srono Kabupaten Banyuwangi - Edy Maskhuri; Minan Jauhari (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
The goal of this study is to ascertain how the Bagorejo Village Government manages its reputation, look at the public relations communication strategies used to enhance that reputation, and take into account the difficulties and potential acts that might affect that reputation. owned by the Bagorejo Village Government. Because the previous Bagorejo Village government did not give back to the community in the sense that it did not provide support when the community carried out an activity within the boundaries of the Bagorejo Village, the community felt that the government had a small role to play in the events that the Bagorejo Village community itself hosted. Therefore, the researcher is interested in learning about the issues in Bagorejo Village. In order to improve public opinion of Bagorejo village, this study aims to determine the public relations communication plan for the community. Moreover, to find out what difficulties the Bagorejo Hamlet PR staff has had in advertising the village. This study combined a qualitative methodology with a kind of field research using descriptive data analysis. The results of this study indicate that Bagorejo Village's public relations heavily rely on the media to boost the village's favorable reputation and to collaborate with the Bagorejo Village community. In addition to using social media, the Bagorejo Village government also uses an approach system through groups in the village and conducts socialization. In addition to socializing with the community, the government also held anjangsana to convey information from Bagorejo village.